PENDIDIKAN MULTIKULTURAL MENUJU MASYARAKAT BERMARTABAT - Bunyamin, Bunyamin (Jurnal Pendidikan Islam, 2016)
This research aims to reveal the depth of multiculturalÂ  education. This study uses qualitative descriptive approach situational analysis. These results indicate the idea of forming system using the concept of multicultural education. , The results of this study can be applied in learning syllabus Religious Education / Akhlaq for high school / boarding school.